ANALISIS POLA LITERASI POLITIK OLEH KOMISI PEMILIHAN UMUM PROVINSI JAMBI TERHADAP PEMILIH PEMULA PADA PEMILU 2024 - Amalia, Dina Fitria; Candra, Alif Aditya; Hendra, Hendra (UNTIRTA CIVIC EDUCATION JOURNAL, 2025)
This study aims to analyze the political literacy patterns carried out by the Jambi Provincial KPU towards new voters in the 2024 election. The main focus of this study is to identify political information needs, search strategies, information communication movements, and product evaluations of the final political process. The method used is a qualitative approach with a descriptive design, collecting data through interviews and documentation. The results of the study indicate that although the KPU has made good efforts to improve political literacy, there are still various obstacles that need to be overcome, such as apathy among young voters and lack of use of social media. The KPU needs to develop a more varied approach and use digital platforms to reach new voters effectively. The recommendations generated from this study are expected to improve the quality and reach of political literacy programs, as well as encourage more active political participation among new voters in Indonesia.Keywords: Political Literacy, First-time Voters, 2024 Election